SATELLITE DNAS, HETEROCHROMATIN AND SEX-CHROMOSOMES IN CHIONODRACO-HAMATUS (CHANNICHTHYIDAE, PERCIFORMES) - T. Capriglione; A. Morescalchi; E. Olmo; ROCCO, Lucia; STINGO, Vincenzo; S. Manzo (Polar Biology, 1994)
We studied the genome of an antarctic ice fish, Chionodraco hamatus, in order to detect highly repetitive DNAs that may play a role in heterochromatinization processes and sex chromosome differentiation. We used two different experimental approaches. Hybridization of a Bkm probe to genomic DNA showed slight differences between the two sexes. Using restriction enzymes, a Bgl II satellite (pIF) was isolated. In situ hybridization revealed a preferential localization of pIF on the centromeres and the telomeres of most chromosomes, as well as an interstitial band on the long arms of the neo-Y sex chromosome, where probably the hypothetical fusion took place. Dot-blot experiments showed that pIF is still present in species belonging to different families of the same suborder. Though preliminary, our results suggest a conservative nature of this DNA which might have played a definite functional role in the genome of these polar fishes. © 1994 Springer-Verlag.